2018
DOI: 10.1021/acs.analchem.8b02384
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Formation of Color Gradients for Glucose Colorimetric Assays on Microfluidic Paper-Based Analytical Devices by Mass Spectrometry Imaging

Abstract: This study describes the use of mass spectrometry imaging with matrix-assisted laser desorption/ionization (MALDI) and desorption electrospray ionization (DESI) to understand the color gradient generation commonly seen in microfluidic paper-based analytical devices (μPADs). The formation of color gradients significantly impacts assay sensitivity and reproducibility with μPADs but the mechanism for formation is poorly understood. The glucose enzymatic assay using potassium iodide (KI) as a chromogenic agent was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 31 publications
0
28
0
2
Order By: Relevance
“…2 These characteristics make paper an ideal platform for point-of-care (POC) with the advantages of high sensitivity, faster analysis time, low-cost, low sample volume, environmental friendliness, exibility and portability. 2 With the development of mPADs, several detection techniques, such as colorimetric change, 3,4 electrochemical properties, 3 light absorption and emission, 5 mass spectrum, 6 and surface-enhanced Raman spectroscopy, 7,8 have been applied to the fabrication of microuidic channels on paper substrates. 9 Among these methods, the advantages of the luminescencebased detection technique integrated with a paper-based device includes low cost, fast detection times, no need for signicant technicians, and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…2 These characteristics make paper an ideal platform for point-of-care (POC) with the advantages of high sensitivity, faster analysis time, low-cost, low sample volume, environmental friendliness, exibility and portability. 2 With the development of mPADs, several detection techniques, such as colorimetric change, 3,4 electrochemical properties, 3 light absorption and emission, 5 mass spectrum, 6 and surface-enhanced Raman spectroscopy, 7,8 have been applied to the fabrication of microuidic channels on paper substrates. 9 Among these methods, the advantages of the luminescencebased detection technique integrated with a paper-based device includes low cost, fast detection times, no need for signicant technicians, and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Of further note is the uniformity of pink color generated over the 1 cm 2 area of the paper sensor when used with a surface distributor. Colorimetric signals generated in traditional µPADs are associated with steep gradients with standard deviations in pixel intensities ranging from 34 to 40% 15 , which makes it difficult to interpret the signal 7 . Recently, it was shown that these gradients arise as a result of wicking fluid pushing small colorimetric molecules to the edge of the detection zones 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Colorimetric signals generated in traditional µPADs are associated with steep gradients with standard deviations in pixel intensities ranging from 34 to 40% 15 , which makes it difficult to interpret the signal 7 . Recently, it was shown that these gradients arise as a result of wicking fluid pushing small colorimetric molecules to the edge of the detection zones 15 . No obvious steep chemical gradients were observed in our glucose sensors utilizing surface distributors, despite using relatively large fluid volumes (57 µl) and sensor surface areas (1 cm 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, multiple stabilisers, such as trehalose (Martinez et al 2007;Gabriel et al 2016), polyvinyl alcohol (Olkkonen et al 2010;Soni and Jha 2015), gelatin (Cha et al 2012;Zhu et al 2014;Liu et al 2019) and dithiothreito (DTT) (Soni and Jha 2017), have been used to ensure long-term stability of the assays. The glucose enzymes have been often spotted onto a substrate (Martinez et al 2007;Santana-Jiménez et al 2018;Dungchai et al 2010;Klasner et al 2010;Gabriel et al 2017;Olkkonen et al 2010;de Freitas et al 2018) though other deposition methods, such as screen printing (Määttänen et al 2011;Lamas-Ardisana et al 2018) and inkjet printing (Abe et al 2010;Wilson et al 2015) take the µPAD a step closer to mass production.…”
Section: Introductionmentioning
confidence: 99%